Ethical Challenges of Using Artificial Intelligence in Global Education Based on Spirituality and Religious Moderation - Sekar Puan Maharani; Febia Ghina Tsuraya; Nurul Azzahra; Maftuhah; Afif Faizin (Islamic Education Management Study Program, Tarbiyah and Teacher Training Faculty, State Islamic University of Madura, 2026)
The digital transformation of the globalization era has accelerated the integration of Artificial Intelligence (AI) into education as a tool for adaptive, efficient, and data-driven learning innovation. AI enables personalized learning, faster evaluation, and broader access to education, but its integration raises ethical challenges such as algorithmic bias, data privacy risks, technology dependency, and the potential dehumanization of learning relationships. This study aims to analyze the ethical challenges of using AI in global education and formulate an ethical framework grounded in spirituality and religious moderation. This study uses a qualitative desk research approach through content analysis of scientific literature and policy documents from the past decade. The findings indicate that while AI increases efficiency and inclusivity, its implementation requires strengthening moral responsibility, justice, and respect for human dignity. Spirituality and religious moderation serve as guiding principles for developing an inclusive and humanistic AI-based education model.